Strategi Pembentukan Akhlak Kedisiplinan Siswa di MAS Al-Ishlahiyah Binjai - Mulyani, Dita; Hemawati; Putra, San (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to explore the strategies and methods used by MAS Al-Ishlahiyah Binjai in shaping students' morals and discipline, because there are indications of students who are less and or not disciplined in following the rules and there are still students who are late. In disciplining students, teachers have a role, so as not to hinder and disturb other students. Therefore, to find out the role of teachers in overcoming indiscipline, research is needed. The research method used is a case study with a qualitative approach, through participatory observation and interviews with teaching staff and students. The purpose of the study is to find out how the efforts made by teachers to provide understanding to students who are indicated as naughty or undisciplined at MAS Al Ishlahiyah Binjai, so that the results of the efforts made to shape MAS Al-Ishlahiyah students to be disciplined can be known.